2017
DOI: 10.3390/jfb8020014
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Red Blood Cells as Potential Photosensitizers in Dye Laser Treatment Against Port-Wine Stains

Abstract: We suggest a novel method that uses artificial blood cells (hemoglobin vesicles, Hb-Vs) as photosensitizers in dye laser treatment (at 595-nm wavelength) for port-wine stains (i.e., capillary malformations presenting as red birthmarks) based on the results of animal experiments. As compared with human red blood cells, Hb-Vs have the same absorbance of 595 nm wavelength light and produce the same level of heat following dye laser irradiation. Small sized Hb-Vs (250 nm) distribute in the plasma phase in blood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Hb-Vs can effectively work in combination with existing phototherapy devices used around the world and there is no need to buy new, expensive laser equipment. 33 Further, they do not result in solar photosensitivity after treatment. 33 As such, the use of Hb-Vs is a suitable treatment for nonmalignant disorders and in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hb-Vs can effectively work in combination with existing phototherapy devices used around the world and there is no need to buy new, expensive laser equipment. 33 Further, they do not result in solar photosensitivity after treatment. 33 As such, the use of Hb-Vs is a suitable treatment for nonmalignant disorders and in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…33 Further, they do not result in solar photosensitivity after treatment. 33 As such, the use of Hb-Vs is a suitable treatment for nonmalignant disorders and in pediatric patients. 33 The creation of artificial RBCs in Japan was originally initiated with the aim of recycling outdated and expired RBCs whose cell membranes have deteriorated over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, creating cell-like structures that mimic the functions of a living cell in a confined space (also known as artificial cells) may give us clues to answer the question. In addition, because artificial cells have a defined molecular composition, they can provide useful platforms to investigate biological phenomena under defined chemical conditions and can serve as tools for multiple biological applications, such as therapeutic techniques, fermentation by artificial cells, the construction of artificial red blood cells, and simplified cell models [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This vacuum‐assisted laser therapy may be used for efficiently destroying small PWS blood vessels. Rikihisa et al put forward a novel approach to improve clinical outcomes of PDL‐resistance PWS. The in vivo results showed that hemoglobin concentration in microvessels was increased significantly through intravenously injection of prepared artificial red cells (hemoglobin vesicles) before laser irradiation, thereby producing more heat to photocoagulate small blood vessels which do not contain enough red blood cells.…”
Section: Introductionmentioning
confidence: 99%